Modeling and economic dispatch of a novel fresh water, methane and electricity generation system considering green hydrogenation and carbon capture - Talaie, Mehdi; Jabari, Farkhondeh; Akbari Foroud, Asghar (Energy conversion and management, 2024)
•Optimization of a green water, Hydrogen, Methane, and power generation system.•Carbon capture from diesel units and green hydrogenation for Methane production.•Use of solar-wind-diesel-hydro units for water, gas, and power generation.•Present mathematical model of water, Hydrogen, Methane, and power generation processes. This paper proposes a novel water, gas and power generation system using wind turbines, solar photovoltaic panels, hydro and diesel units. A power to gas technology composed of a carbon capture unit, an electrolizer, a hydrogen storage, and a methanation process, is used to supply the natural gas demand of an industrial microgrid. The electricity is consumed by a desalination unit to procure the water demand, electrolizer inflow, and charge the water storage. A mixed integer nonlinear optimization problem is developed to minimize daily operation cost of hydro units, fuel cost of diesel engines, and cost of electrical power purchased from local grid. A 1-year study with 12 extreme operational conditions is carried out to validate its resiliency and flexibility in warm and windy coastal area of Kish. Minimum and maximum objective functions are 2320 and 6797 $ during April and August, respectively. Maximum values of power purchased/sold from/to local grid are obtained as 6.12/9.18 MW at hours 3 and 15 of April as well as 1.2/3.55 MW at hours 22 and 14 of August, respectively. Lower renewables products and higher loads are caused to lower power selling to distribution company during summer days of August, and vice versa during April with higher wind and solar products and lower demands. Electricity consumption of desalination, carbon capture, electrolizer and pump under peak water (1.866 million Liter) and gas (1.827 MW) loads during August are higher than those of April with light loads (maximum 841.1 m3 water and 875.6 kW gas demand).